BUDAYA ORGANISASI SEKOLAH DAN MOTIVASI BERPRESTASI DENGAN KINERJA GURU PADA SEKOLAH DASAR NEGERI GUGUS ADIARSA KARAWANG BARAT - Isnaeni Wuryantina, Isnaeni Wuryantina (Pascasarjna Universitas Negeri Jakarta, 2015)
Abstract: The objective of this research is to obtain information the correlation between of organization culture school and achievement motivation with performance of the teacher elementary school cluster Adiarsa in distric of West Karawang. The approach used was quantitative by survey method in elementary school cluster Karangpawitan in distric of West Karawang. The sample collect from 40 teacher of elementary school who obtained with random technique, through an instrument that has been validated a questionnaire using scale likert 1-5. Then the data were analyzed by using regression. The research findings are: (1) there is correlation organization culture school with performance; (2) there is correlation achievement motivation with performance; (3) there is correlation organization culture school and achievement motivation with performance. The result of the research implied that in the organization culture school, the achievement motivation, the quality of Performance.Â Keywords: organization culture school, achievement motivation, performanceÂ Abstrak: Tujuan dari penelitian ini adalah untuk mendapatkan informasi korelasi antara sekolah budaya organisasi dan motivasi berprestasi dengan kinerja Adiarsa gugus guru sekolah dasar di kecamatan dari Karawang Barat. Pendekatan yang digunakan adalah kuantitatif dengan metode survey di SD gugus sekolah Karangpawitan di distric dari Karawang Barat. Sampel mengumpulkan dari 40 guru sekolah dasar yang diperoleh dengan teknik random, melalui instrumen yang telah divalidasi kuesioner menggunakan skala Likert 1-5. Kemudian data dianalisis dengan menggunakan regresi. Temuan penelitian adalah: (1) ada sekolah budaya organisasi korelasi dengan kinerja; (2) ada motivasi berprestasi korelasi dengan kinerja; (3) ada sekolah budaya organisasi korelasi dan motivasi berprestasi dengan kinerja. Hasil penelitian yang tersirat bahwa di sekolah budaya organisasi, motivasi berprestasi, kualitas kinerja.Â Kata kunci: sekolah budaya organisasi, motivasi berprestasi, kinerja